MCSA 70-740 cert guide : installation, storage, and compute with Windows Server 2016 - Sequeira, Anthony (Pearson, 2017)
This is the eBook version of the print title. Note that the eBook does not provide access to the practice test software that accompanies the print book. Access to the appendixes and video lessons is available through product registration at Pearson IT Certification; or see instructions in back pages of your eBook. Learn, prepare, and practice for MCSA 70-740 exam success with this Cert Guide from Pearson IT Certification, a leader in IT certification. Master MCSA 70-740 exam topics Assess your knowledge with chapter-ending quizzes Review key concepts with exam preparation tasks Learn from more than one hour of video lessons MCSA 70-740 Cert Guide is a best-of-breed exam study guide. Leading technology trainer and consultant Anthony Sequeira shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills. Material is presented in a concise manner, focusing on increasing your understanding and retention of exam topics. The book presents you with an organized test preparation routine through the use of proven series elements and techniques. Exam topic lists make referencing easy. Chapter-ending Exam Preparation Tasks help you drill on key concepts you must know thoroughly. Review questions help you assess your knowledge, and a final preparation chapter guides you through tools and resources to help you craft your final study plan. Well regarded for its level of detail, assessment features, and challenging review questions and exercises, this study guide helps you master the concepts and techniques that will allow you to succeed on the exam the first time. The study guide helps you master all the topics on the MCSA 70-740 exam, including: Windows Server installation in host and compute environments, including Nano Server Storage: configuring disks and volumes, implementing server storage, and data duplicationHyper-V implementation, including VM settings, storage, and networking Windows container deployment and management High availability: HA/DR options, failover clustering, Storage Spaces Direct, VM movement, and network load balancing Server environment maintenance and monitoring.